Restricting the participation of lay judges in adjudicating civil cases - as a violation of democracy - Adamiec-Witek, Mariola (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*102.14px); top: calc(var(–scale-factor)*242.91px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.9942);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*121.70px); top: calc(var(–scale-factor)*242.91px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.05683);" role="presentation">author discusses the provisions limiting the p<span dir="ltr" style="left: calc(var(–scale-factor)*51.72px); top: calc(var(–scale-factor)*253.23px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.12853);" role="presentation">art<span dir="ltr" style="left: calc(var(–scale-factor)*63.24px); top: calc(var(–scale-factor)*253.23px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998244);" role="presentation">icipation of lay judges in adjudicating in civil cases introduced <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*263.58px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.990035);" role="presentation">in 2021, indicates the effects of this regulation on adjudication and <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*274.02px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.02108);" role="presentation">the reaction of legal circles to the introduction of this regulation - <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*284.34px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0114);" role="presentation">with emphasis on the violation of democracy as a result of these <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*294.66px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.05231);" role="presentation">changes. The author also indicates how the legislation - <span dir="ltr" style="left: calc(var(–scale-factor)*280.01px); top: calc(var(–scale-factor)*294.66px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.898714);" role="presentation">since <span dir="ltr" style="left: calc(var(–scale-factor)*46.80px); top: calc(var(–scale-factor)*304.98px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998333);" role="presentation">Poland <span dir="ltr" style="left: calc(var(–scale-factor)*79.90px); top: calc(var(–scale-factor)*304.98px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998036);" role="presentation">regained <span dir="ltr" style="left: calc(var(–scale-factor)*119.58px); top: calc(var(–scale-factor)*304.98px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.962308);" role="presentation">independence - <span dir="ltr" style="left: calc(var(–scale-factor)*187.70px); top: calc(var(–scale-factor)*304.98px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.012);" role="presentation">regulated <span dir="ltr" style="left: calc(var(–scale-factor)*230.28px); top: calc(var(–scale-factor)*304.98px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.993);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*248.39px); top: calc(var(–scale-factor)*304.98px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.881571);" role="presentation">issue <span dir="ltr" style="left: calc(var(–scale-factor)*273.09px); top: calc(var(–scale-factor)*304.98px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0325);" role="presentation">of <span dir="ltr" style="left: calc(var(–scale-factor)*286.76px); top: calc(var(–scale-factor)*304.98px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.993);" role="presentation">the p<span dir="ltr" style="left: calc(var(–scale-factor)*51.72px); top: calc(var(–scale-factor)*315.42px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.12853);" role="presentation">art<span dir="ltr" style="left: calc(var(–scale-factor)*63.24px); top: calc(var(–scale-factor)*315.42px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.998496);" role="presentation">icipation of the so-<span dir="ltr" style="left: calc(var(–scale-factor)*133.94px); top: calc(var(–scale-factor)*315.42px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.00814);" role="presentation">called social factor in adju<span dir="ltr" style="left: calc(var(–scale-factor)*235.01px); top: calc(var(–scale-factor)*315.42px); font-size: calc(var(–scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(1.0341);" role="presentation">dication.